2011
DOI: 10.1002/chem.201003255
|View full text |Cite
|
Sign up to set email alerts
|

Lanthanide‐Containing Photoluminescent Materials: From Hybrid Hydrogel to Inorganic Nanotubes

Abstract: Functional photoluminescent materials are emerging as a fascinating subject with versatile applicability. In this work, luminescent organic-inorganic hybrid hydrogels are facilely designed through supramolecular self-assembly of sodium cholate, and lanthanide ions such as Eu(3+), Tb(3+), and Eu(3+)/Tb(3+). Fluorescence microscopy and TEM visualization demonstrates the existence of spontaneously self-assembled nanofibers and 3D networks in hybrid hydrogel. Photoluminescence enhancement of lanthanide ions is rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
62
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(62 citation statements)
references
References 70 publications
0
62
0
Order By: Relevance
“…Numerous studies have been performed on the effects of salts, pH, metal ions, and amino acids on the properties of NaDC hydrogels. 20,22,23 The existing results explicitly elucidate how these additives essentially affect the properties of NaDC hydrogels. Jover et al prepared NaDC hydrogels in a phosphate buffer solution (PBS) and reported that the viscoelasticity of the hydrogel from NaDC in PBS increased drastically with an increase in NaCl concentration.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have been performed on the effects of salts, pH, metal ions, and amino acids on the properties of NaDC hydrogels. 20,22,23 The existing results explicitly elucidate how these additives essentially affect the properties of NaDC hydrogels. Jover et al prepared NaDC hydrogels in a phosphate buffer solution (PBS) and reported that the viscoelasticity of the hydrogel from NaDC in PBS increased drastically with an increase in NaCl concentration.…”
Section: Introductionmentioning
confidence: 99%
“…The metal coordination of fatty acids and steroids has been widely used to produce organogels during the past two decades . One successful example is the use of steroidal compounds such as a bile salt to complex with a series of metal cations in an aqueous solution to generate a supramolecular hydrogel . Inspired by an early study on metal‐bile salt supramolecular self‐assembly, we occasionally found that ophthalmic steroidal drugs (e.g., sodium phosphate dexamethasone, succinated dexamethasone) could form a supramolecular hydrogel for “self” delivery by the addition of various metal cations, such as Ca 2+ , Zn 2+ , and Mg 2+ .…”
Section: Ophthalmic Hydrogel Systemmentioning
confidence: 99%
“…Fluoride compounds with general formulae of ALnF 4 or LnF 3 (A: alkaline metal; Ln: lanthanide element) offer multiple advantages such as high transparency, large band gap, chemical stability, and low phonon energy minimizing the multiphonon relaxation and improving the luminescence efficiencies [13][14][15]. Synthesis of Eu-based fluoride compounds, such as NaEuF 4 and EuF 3 structures with different phases, shapes and sizes can be achieved by means of various synthetic approaches such as hydrothermal [11,16,17], sonochemical [18], and wet chemical routes [19,20], as well as sol-gel techniques [5,21,22]. At the same time, there have been just a few publications exploring hydrogels, aerogels or cryogels including lanthanide ions [5,21,22].…”
Section: Introductionmentioning
confidence: 99%
“…Synthesis of Eu-based fluoride compounds, such as NaEuF 4 and EuF 3 structures with different phases, shapes and sizes can be achieved by means of various synthetic approaches such as hydrothermal [11,16,17], sonochemical [18], and wet chemical routes [19,20], as well as sol-gel techniques [5,21,22]. At the same time, there have been just a few publications exploring hydrogels, aerogels or cryogels including lanthanide ions [5,21,22]. The latter are highly porous inorganic structures of extremely low density.…”
Section: Introductionmentioning
confidence: 99%